(untitled) (Transmediterranean History, 2021)
In 984, Gerbert d’Aurillac exchanged three letters with fellow churchmen, which mention manuscripts dealing with arithmetic and astronomy. On this basis, this contribution traces a broader transfer of mathematical and astronomical knowledge from the Arabic-Islamic to the Latin-Christian sphere in the late- tenth century. Addressing the so-called “dark legend” of Gerbert, the earliest corpus of Latin works on the astrolabe, the abacus, and Hindu-Arabic numerals, as well as evidence for exchange between scholarly milieus in Umayyad al-Andalus and Catalonia, it discusses Gerbert’s direct involvement in this transfer.